thurnauer: vt and vi, to paint in the second person - Mengham, Rod (Text Matters: A Journal of Literature, Theory and Culture, 2015)
Many of the figures in Thurnauer’s paintings who fix us with their gaze have been borrowed from the work of Manet, the artist who organized so many of his paintings around a face-to-face confrontation of viewer and work. The painting returns the viewer’s gaze with total impartiality, making us see our own motives and investments more than the illusion that the figure in the painting will accommodate them.Issues of language often surface literally in paintings by Thurnauer; written language appears sometimes as part of the material fabric in which human figures move or recline. The textual elements are not superimposed on the figures but appear to exist in the world they inhabit, requiring the painter to relate figure to ground in a process of interlacing. When the viewer’s eye traverses the painting it falls under the magnetic influence of the text to the extent that viewing must succumb in some degree to the operations of reading with its specific rhythms and expectations.In these paintings, visual and verbal languages provide us with different maps of the same territory; and Thurnauer’s hybridized representations argue that the world can only be rendered through a dialogue, an interlocution of different forms, genres, media. We approach her work, not as viewers whose function is predicated through a gaze regulated according to the distorting demands of consumption or control, but as readers engaged in a critical activity seeing around the edges of historically produced versions of the self.